THE USE OF PICTORIAL DISCOURSE FOR HEALTH WARNINGS ON THE DANGERS OF TOBACCO PACKAGES (PENGGUNAAN WACANA GAMBAR SEBAGAI PERINGATAN KESEHATAN TENTANG BAHAYA MEROKOK) - Bram Denafri; Amelia Yuli Astuti; Sabri Koebanu (Universitas PGRI Sumatera Barat, 2020)
The Indonesian government promotes discourse on the health dangers of smoking by pasting pictures on cigarette packages to reduce the number of smokers in Indonesia. Therefore, this research uses pictorial discourse on cigarette packaging to provide health warning messages to smokers of kretek packaged cigarettes. This is portrait research with data obtained through observations at the Kretek Museum, Kudus, Central Java, and the Ministry of Health followingRegulation Number 56 of 2017 and analyzed using the BREAK theory. Based on the data and analysis, the primary and secondary discourses use scary images as well as pictures of fruits and plants, respectively. The general type of movement of primary and secondary discourse is DIKO (essence divergent and spiritually convergent)